Salivary lipid peroxidation and total sialic acid levels during healthy gestation and postpartum: A longitudinal study - YARAT, AYŞEN; AKYÜZ, SERAP HATİCE (PERGAMON-ELSEVIER SCIENCE LTD, 2010)
Objectives: This study investigated salivary lipid peroxidation (LPO) as an oxidative stress marker and salivary total sialic acid (TSA) as an inflammatory response during gestation and postpartum. Design and methods: Salivary LPO and TSA levels, using the Ledwozyw and Warren methods respectively, were obtained in healthy pregnant women followed up during gestation and 6-8 weeks postpartum, and in healthy non-pregnant controls. All were with good oral health. Results: LPO was significantly higher than controls during all trimesters and postpartum and in the second trimester than in the third trimester and postpartum. TSA in the second trimester was significantly higher than in any other group. First trimester levels were significantly higher than postpartum. Oral health indices remained within normal levels for the duration. Conclusion: The salivary LPO profile followed plasma gestation and postpartum profiles in the literature but the salivary TSA differed in that after the 2nd trimester, rather than persisting, it decreased. (C) 2009 The Canadian Society of Clinical Chemists. Published by Elsevier Inc. All rights reserved.
Keywords: Saliva; Lipid peroxidation; N-acetylneuraminic acid; Pregnancy; Postpartum; PROTEIN ALPHA-1-ACID GLYCOPROTEIN; NORMAL HUMAN-PREGNANCY; C-REACTIVE PROTEIN; HUMAN WHOLE SALIVA; PLASMA; SERUM; NEURAMINIDASE; PERIODONTITIS; SIALYLATION; SECRETION